Pengaruh Content Marketing dan Electronic Word of Mouth (E-WoM) pada Media Sosial Tiktok Shop Terhadap Keputusan Pembelian Produk Skincare Generasi Z Kota Bengkulu - Atika Anggreani; Veny Puspita; Markoni Markoni (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims find out how big influence content marketing Electronic Word of Mouth (e-WoM) TikTok shop social media purchasing decisions Generation Z skincare products Bengkulu City. research sample 160 Generation Z respondents Bengkulu City purchased skincare products TikTok shop social media. analysis data collection questionnaire Likert scale. results t test results, calculated t value content marketing variable (X1) is 7.329 with α = 0.001 < α = 0.05, means H0 is rejected, and Ha is accepted, content marketing variable has an influence on purchasing decisions (Y). calculated t value electronic word of mouth variable (X2) is 5.214 with α = 0.001 < α = 0.05, H0 is rejected, and Ha is accepted, electronic word of mouth variable influence on purchasing decisions (Y). From results F test, the calculated F is 196.632 with α = 0.001 < α = 0.005, this H0 is rejected, and Ha accepted. Overall, influence of content marketing, electronic word of mouth on TikTok shop social media purchasing decisions Generation Z skincare products Bengkulu City